ANALISIS TERHADAP PERLINDUNGAN PEMILIK SAHAM MINORITAS DITINJAU DARI HUKUM INDONESIA - Husna, Alifa; Adriaman, Mahlil (Ensiklopedia of Journal, 2024)
Knowledge of corporate law recognizes the principle of "Majority Rule Minority Protection". This principle emphasizes that minority shareholders pay attention to their interests and rights. This is due to their minority position, their rights tend to be less protected than the majority shareholders. Legal protection for the majority shareholder is sufficiently guaranteed, especially through the GMS. Meanwhile, protection for minorities is something new and has received less attention. The problem in this study is the regulation of laws against minority shareholders in public companies in Indonesia and how legal remedies from minority shareholders are related to violations of their rights. This research is a normative research with a descriptive research type. The approach used is normative juridical. Data collection is done by literature study and document study. The data used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The collected data is then analyzed qualitatively. The results of this study are that in terms of shareholders in Indonesia the regulation is contained in Law Number 40 of 2007 concerning PT which then includes the element of PT. There are shareholders, commissioners, and also directors whose highest sovereignty for decision making is at the GMS (General Meeting of Shareholders). Then in legal protection for minority shareholders there is the right to sue, the right to access information, the right to run the company, the right to fair treatment. And also in principle there is equal protection, namely the principle that tends to give equal voice and rights to shareholders and of course this principle is contained in article 53 paragraph 2 of Law Number 40 of 2007.Keywords: Legal Protection, Minority Shareholders, Public Companies